Cataplexy in a patient treated for prolactinoma: Case report - Nikolić-Djurović, Marina; Pereira, Albero M.; Jeumović, Zvezdana; Pavlović, Dragan; Janković, Dragana; Petakov, Milan; Čivčić, Milorad; Vasović, Olga; Damjanović, Svetozar (Vojnosanitetski pregled, 2017)
Introduction. Isolated cataplexy, without the presence of narcolepsy, is a relatively rare condition, and can be regarded as attacks of motor inhibition with loss of muscle tone and areflexia. The diagnosis of cataplexy relies on the clinical presentation and medical history and it is rarely confirmed by video-polygraph. We here described a female patient treated for prolactinoma who developed isolated cataplexy. Case report. A 53-year-old female treated with bromocriptine for a macroprolactinoma presented with sudden episodes of weakness and toneless legs leading to falls and injuries on several occasions. Cardiovascular evaluation was completely normal. Psychiatric evaluation showed no psychotic phenomenology or suicidal ideas. Pituitary imaging showed empty sella with a remnant sellar mass with infra- and parasellar extension. Neurological examination revealed mild obstructive sleep hypopnea/apnea. Electroencephalographic monitoring during sleep and awakening did not show appearance of epi potentials. HLA haplotyping was positive for HLA-DR3,16;DR51;DQ1 allele, confirming a diagnosis of isolated cataplexy. Treatment included tricyclic antidepressants and reduction of bromocriptine dosage with resolution of cataplexy. Conclusion. We reported the first case of isolated cataplexy most probably associated with dopamine agonist treatment for prolactinoma.
Keywords: prolactinoma; pituitary neoplasms; cataplexy; comor-bidity; diagnosis; magnetic resonance imaging; genet-ics; medical; treatment outcome